THE EFFECT hCG (human Chorionic Gonadotropin) TO OVULATION AND HATCHING OF FISH EGG OF COMET(Carassius auratus) - Adi Andana; Nuraini Nuraini; Sukendi Sukendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThis research was conducted from February to March 2018 in the halls 0f the fishery seeds TarantangSubsdistrict, Harau, West Sumatra Province. The aims of this research was to know the effect of hCG (Human Chorionic Gonadotropin) pituitary gland injected with different dose on ovulation and survival rate of comet (Carassius auratus)and To find the best dose ot the pituitary gland to stimulate ovulation and survivaln rate of comet (Carassius auratus).The treatment used is as follows : PO Control using NaCL 0,9 % as much 0,2 ml/kg weight of test fish. P1: Injection of hCG with dose 700 IU/kg weight of test fish. P2: Injection of hCG with dose 900 IU/kg weight of test fish. P3: Injection of hCG with dose 1100 IU/kg weight of test fish.The best result of the research is P2: Injection of hCG with dose 900 IU/kg weight of test fish the with an average latent time 6 hours and 3 minutes, amount eggs(items)/g 219 items,Fertilization Rate 73,28%, Hatching Rate 75,64%, Survival Rate (SR)7 91,22%.Keywords :hCG hormone, Ovulation, Latent time, Carassiusauratus